Improved Direct Torque Control (DTC) Performances Of Induction Machine Using Cascaded H-Bridge Multilevel Inverter - Ramahlingam, Sundram (UTeM, 2017)
Excellent torque control has been a focus of research in AC drives since last decades due to its important requirements for many industrial applications. Spurred on by rapid developments in the embedded computing systems, two popular approaches namely Field Oriented Control (FOC) and Direct Torque Control (DTC) were used to obtain excellent torque control. Obviously, both approaches use the space vector modulation (SVM) technique to reduce torque ripples as well as produce a constant switching frequency. However, the use of SVM complicates the control structures of FOC and DTC, which somehow increase the sensitivity control and hence may degrade the control’s accuracy. Moreover, the selection of voltage vectors is inappropriate, particularly for application of two-level inverter which offers limit number of voltage vectors. This thesis aims to reduce torque ripple and produce a constant switching frequency in DTC by replacing the hysteresis controller and two-level inverter with a PI based torque controller and three level cascaded H-Bridge multilevel inverter (CHMI), respectively. By employing the three level CHMI, it provides a greater number of voltage vectors as compared to that offered in the conventional two-level inverter which gives more options to select the most optimal voltage vectors. The analysis of effects of selecting different voltage vectors on DTC performances are carried out to identify the most optimal vectors that can be chosen to improve torque control performances for every operating condition. The identification is made with the aid of vector diagrams and some equations, i.e. equations of torque rate, slip angular frequency and torque capability. This thesis also presents detail explanation and calculation of optimal PI parameter tuning strategy consecutively to improve torque control with reduced torque ripples. The proposed DTC control algorithm can be optimally executed at high computation rate by totally using C-coding with DS1104 controller board. The effectiveness of the proposed method is verified via simulation and experiment results, as well as comparison with the conventional DTC method. The results have shown that the torque ripple in the proposed method can be greatly reduced about 9.54%.